Morphological and Mechanical Properties of the Human Patella Tendon in Adult Males With Achondroplasia - Sims, David T.; Onambélé-Pearson, Gladys L.; Burden, Adrian; Payton, Carl; Morse, Christopher I. (Frontiers in Physiology, 2018)
Achondroplasia is a genetic mutation of fibroblast growth factor receptor resulting in impaired growth plate development in long bones due to lower collagen turnover. Despite the characteristic shorter stature and lower strength in Achondroplasic groups, little is known of the tendon mechanical properties under contraction. The aim of this study was to therefore to conduct a between measure design of patella tendon (PT) mechanical properties (stress, strain, stiffness and Young’s Modulus) in 10 men with Achondroplasia (22 3 yrs) and 17 male controls (22 2 yrs). PT mechanical properties were measured during isometric maximal voluntary contraction (iMVC) using ultrasonography. The Achondroplasic group produced 54% less stress at iMVC than controls (29.4 ±8.0 v 64.5 ±14.0 MPa, P < 0.001, d = 3.12). Maximal excursion of the Achondroplasic PT was 22% less than controls at iMVC (7.4 ±2.1 v 5.5 ±1.7 mm, P < 0.001, d = 0.99), but there was no difference in strain between groups (13 ±4 v 13 ±3%, P > 0.05). Achondroplasic PT were 47% less stiff (748 ±93 v 1418 ±101 N·mm-1, P < 0.001, d = 6.89) and had a 51% lower Young’s modulus (0.39 ±0.09 v 0.77 ±0.14 GPa, P < 0.001, d = 3.46) than controls at iMVC. Achondroplasic PT are indeed more compliant than controls which may contribute to lower relative force production. The causes of higher Achondroplasic PT compliance are unclear but are likely due to the collagen related genetic mutation which causes Achondroplasia.